Human Fetal Exposure to Triclosan and Triclocarban in an Urban Population from Brooklyn, New York - Pycke, Benny F. G. (American Chemical Society, 2014)
[Image: see text] Triclosan (TCS) and triclocarban (TCC) are antimicrobial agents formulated in a wide variety of consumer products (including soaps, toothpaste, medical devices, plastics, and fabrics) that are regulated by the U.S. Food and Drug Administration (FDA) and U.S. Environmental Protection Agency. In late 2014, the FDA will consider regulating the use of both chemicals, which are under scrutiny regarding lack of effectiveness, potential for endocrine disruption, and potential contribution to bacterial resistance to antibiotics. Here, we report on body burdens of TCS and TCC resulting from real-world exposures during pregnancy. Using liquid chromatography tandem mass spectrometry, we determined the concentrations of TCS, TCC, and its human metabolites (2′-hydroxy-TCC and 3′-hydroxy-TCC) as well as the manufacturing byproduct (3′-chloro-TCC) as total concentrations (Σ−) after conjugate hydrolysis in maternal urine and cord blood plasma from a cohort of 181 expecting mother/infant pairs in an urban multiethnic population from Brooklyn, NY recruited in 2007–09. TCS was detected in 100% of urine and 51% of cord blood samples after conjugate hydrolysis. The interquartile range (IQR) of detected TCS concentrations in urine was highly similar to the IQR reported previously for the age-matched population of the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2004, but typically higher than the IQR reported previously for the general population (detection frequency = 74.6%). Urinary levels of TCC are reported here for the first time from real-world exposures during pregnancy, showing a median concentration of 0.21 μg/L. Urinary concentrations of TCC correlated well with its phase-I metabolite ∑-2′-hydroxy-TCC (r = 0.49) and the manufacturing byproduct ∑-3′-chloro-TCC C (r = 0.79), and ∑-2′-hydroxy-TCC correlated strongly with ∑-3′-hydroxy-TCC (r = 0.99). This human biomonitoring study presents the first body burden data for TCC from exposures occurring during pregnancy and provides additional data on composite exposure to TCS (i.e., from both consumer-product use and environmental sources) in the maternal–fetal unit for an urban population in the United States.